„Sala samobójców” jako obraz współczesnej młodzieży uwikłanej w wirtualnej rzeczywistości - Kanclerz, Bożena (Kultura-Społeczeństwo-Edukacja, 2016)
The aim of this article is to analyze the contexts of teaching in the film „Suicide room”. At the outset they presented examples of the role of film in education. Subsequently was presented story of the film. An essential part of the article states while presenting the meanings of pedagogy we could see in the film. First of all, „Suicide Room” is a film whose story is firmly anchored in the contemporary world entangled in the net, with particular emphasis on two phenomena: cyberbullying and addiction to the virtual world. The film Suicide Room is also an interesting picture of the family. Also in the subjective reception, it is a film about loneliness and lost in the harsh reality of the modern world. This is an interesting picture being a prelude to multi-context discussion of the condition of individuals, families and generations living in the postmodern society.